Interview with Dr. Roberto Elias: knowing the future of dentistry for special patients - Falconí Salazar, Edith (2021)
In this interview, Dr. Roberto Elias reveals how dental work with special patients was the main driver for the foundation of AIOPE (Inter-American Academy of Dentistry for Special Patients). The main objective of this association is to develop academic activities that support health-oriented and related institutions, as well as to propose protocols and public policies to improve living conditions of people with disabilities. Likewise, it highlights the importance of sharing different experiences among specialists from all over America and the importance of incorporating courses during university education both in undergraduate and graduate degrees to improve the oral health of people with disabilities. In addition, teamwork stands out, as well as knowing and listening to every disabled patient, respecting their physical, mental, sensorial and behavioral condition in order to humanize the dental profession dedicated to a vulnerable population.